Analisa Pengaruh Volume Kendaraan dan Kecepatan Terhadap Tingkat Kebisingan Lalu Lintan di Jalan Cikuray, Garut - Ni Made Widya Pratiwi; Putu Budiarnaya; Regina Ezzelif Herlambanga; Komang Agus Ariana (Reinforcement Review in Civil Engineering Studies and Management, 2022)
Cikuray street, Garut is a collector road located 1 km from Garut Square, and on this road, there are many offices and shops for facilities and services. Therefore, Cikuray street experiences an increase in a traffic flow which causes noise. This study aims to analyze the level of traffic noise due to the volume and speed of vehicles. The method used in this research is a direct survey of the field and traffic noise modeling analysis using multiple linear regression analysis with the help of SPSS (Statistical Package of the Social Sciences) software version 26 for Windows. From the analysis, the highest volume of vehicles occurred on Saturday at 11,605 pcu/hour, with the average speed ranging from 34.00 – 38.00 km/hour and for a noise level of 84.55 dB(A) which means it has exceeded the standard. limit. permissible noise level. The relationship between volume and vehicle speed to traffic noise levels on Jalan Cikuray Garut using mathematical modeling is shown in the equation Y = 56.777 + 0.020X1 + 0.043X2 + 0.214X3 – 0.090X4 with R2 = 0.443. This shows that traffic noise (Y) can be explained by the volume of motorcycles (X1), the volume of light vehicles (X2), the volume of heavy vehicles (X3), and traffic speed (X4).